Human Milk Oligosaccharides: A Comprehensive Review towards Metabolomics - Laura Corona; Anna Lussu; Alice Bosco; Roberta Pintus; Flaminia Cesare Marincola; Vassilios Fanos; Angelica Dessì (MDPI AG, 2021)
Human milk oligosaccharides (HMOs) are the third most represented component in breast milk. They serve not only as prebiotics but they exert a protective role against some significant neonatal pathologies such as necrotizing enterocolitis. Furthermore, they can program the immune system and consequently reduce allergies and autoimmune diseases' incidence. HMOs also play a crucial role in brain development and in the gut barrier's maturation. Moreover, the maternal genetic factors influencing different HMO patterns and their modulation by the interaction and the competition between active enzymes have been widely investigated in the literature, but there are few studies concerning the role of other factors such as maternal health, nutrition, and environmental influence. In this context, metabolomics, one of the newest "omics" sciences that provides a snapshot of the metabolites present in bio-fluids, such as breast milk, could be useful to investigate the HMO content in human milk. The authors performed a review, from 2012 to the beginning of 2021, concerning the application of metabolomics to investigate the HMOs, by using Pubmed, Researchgate and Scopus as source databases. Through this technology, it is possible to know in real-time whether a mother produces a specific oligosaccharide, keeping into consideration that there are other modifiable and unmodifiable factors that influence HMO production from a qualitative and a quantitative point of view. Although further studies are needed to provide clinical substantiation, in the future, thanks to metabolomics, this could be possible by using a dipstick and adding the eventual missing oligosaccharide to the breast milk or formula in order to give the best and the most personalized nutritional regimen for each newborn, adjusting to different necessities.